Analysis of burst pressure on elbow and t-section in the presence of defect - Adzmil, Abdul Aziz (2013)
This study focuses on the development of short hydrostatic burst model of PVC fittings and their analysis. The experiments of burst pressure for fittings are hardly can be seen to be carried out either by industry or by researchers and especially for PVC fittings. This situation exists because of many reasons. One of them is the difficulty of getting a superb; zero leaks for PVC material. As for example, in hydrostatic burst test that involves metal, the technique of welding and thread are widely available for them for the jointing procedures. As for PVC cement, the most practical jointing procedure is only by using PVC cement. However, this method has high probability of leakage even if any small mistake done during the jointing process. In addition, parallel to the low pressure application of PVC fittings, there is no requirement in industry to have data on the PVC fittings burst pressures. After a well reliable model design is achieved, and then the main focus is to observe and analyze the effect of defected PVC model on its burst pressure. This is the main objective in this analysis. In a circuit of PVC piping installation, the is small probability for the fittings to break due to internal pressure as the thinner and weaker straight pipe will breaks first. However, in the presence of defect on fittings, the piping break can occur on fittings. In the experimental analysis, both perfect and defected fitting are to be obtained their burst pressures. Analysis will be carried out on both data to see the pattern of effect of defected fittings and also able to predict its left strength using previous solution. The expected result produces from the experiment is the burst pressure of the PVC fittings will be getting lower as the depth of defect introduced increases. Defected fittings will be less resistant to internal pressure.